Sequencing Analysis of Invasive Carbapenem-Resistant Klebsiella pneumoniae Isolates Secondary to Gastrointestinal Colonization - Gaetano Maugeri; Maddalena Calvo; Dafne Bongiorno; Dalida Bivona; Giuseppe Migliorisi; Grete Francesca Privitera; Guido Scalia; Stefania Stefani (Microorganisms)
Klebsiella pneumoniae represent a common invasive infection etiological agent, whose potential carbapenem-resistance and hypermucoviscosity complicate the patient’s management. Infection development often derives from gastrointestinal colonization; thus, it is fundamental to monitor asymptomatic K. pneumoniae colonization through surveillance protocols, especially for intensive care and immunocompromised patients. We described a six-month routine screening protocol from the Policlinico of Catania (Italy), while blood samples were collected from the same patients only in cases of a systemic infection suspicion. All the patients who had dissemination episodes were furtherly investigated through next-generation sequencing, analyzing both colonizing and disseminating strains. This study documents emerging invasive sequence types such as ST101, ST307, and ST395, mainly revealing blaNDM or blaKPC genes, along with siderophores and hyperproduction capsule markers as virulence factors. Most of the detected factors are presumably related to a specific plasmid content, which are extremely varied and rich. In conclusion, active surveillance through sequencing is essential to enhance awareness of local epidemiology within high-risk multi-drug resistance areas. A random sequencing analysis on the most warning microorganisms could enhance sequence typing (ST) awareness within specific settings, allowing for better prevention control strategies on their eventual persistence or diffusion.